2022
DOI: 10.1038/s41467-022-34094-y
|View full text |Cite
|
Sign up to set email alerts
|

Translation and natural selection of micropeptides from long non-canonical RNAs

Abstract: Long noncoding RNAs (lncRNAs) are transcripts longer than 200 nucleotides but lacking canonical coding sequences. Apparently unable to produce peptides, lncRNA function seems to rely only on RNA expression, sequence and structure. Here, we exhaustively detect in-vivo translation of small open reading frames (small ORFs) within lncRNAs using Ribosomal profiling during Drosophila melanogaster embryogenesis. We show that around 30% of lncRNAs contain small ORFs engaged by ribosomes, leading to regulated translati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 73 publications
0
31
0
Order By: Relevance
“…ORFs in Drosophila has been demonstrated using ribosomal profiling (Aspden et al, 2014;Patraquim et al, 2022), and pervasive transcription has also shown to evolve new functional protein (Ruiz-Orera et al, 2018). Overall, we observed all possible combinations of features to be involved in the creation of new ORFs, implying that there are many different paths giving rise to new ORFs.…”
Section: Enabling Mutationsmentioning
confidence: 59%
See 1 more Smart Citation
“…ORFs in Drosophila has been demonstrated using ribosomal profiling (Aspden et al, 2014;Patraquim et al, 2022), and pervasive transcription has also shown to evolve new functional protein (Ruiz-Orera et al, 2018). Overall, we observed all possible combinations of features to be involved in the creation of new ORFs, implying that there are many different paths giving rise to new ORFs.…”
Section: Enabling Mutationsmentioning
confidence: 59%
“…Furthermore, the here reported abundance of mainly short ORFs in non-coding DNA makes it likely that many are randomly translated (Ingolia et al, 2014). Indeed, the coding potential of thousands of small ORFs in Drosophila has been demonstrated using ribosomal profiling (Aspden et al, 2014; Patraquim et al, 2022), and pervasive transcription has also shown to evolve new functional protein (Ruiz-Orera et al, 2018). Overall, we observed all possible combinations of features to be involved in the creation of new ORFs, implying that there are many different paths giving rise to new ORFs.…”
Section: Discussionmentioning
confidence: 99%
“…However, up to 0.3 micropeptides might exist per transcribed lncRNA, which is significant for a molecular species characterized by its noncoding character. Up to 7000 micropeptides can be expected to be expressed in the human genome [ 52 ]. Currently, only 10% of these are already quantifiable, and most need to be functionally tested [ 53 ].…”
Section: New Concepts Of Long Noncoding Rnas Function With Potential ...mentioning
confidence: 99%
“…Comparative analyses of translation properties and molecular and evolutionary signatures of these translated smORFs have revealed the existence of distinct classes of smORFs which could represent different stages of smORF functionalization (Aspden et al, 2014;Couso and Patraquim, 2017;Patraquim et al, 2022). This classification suggested the existence of five different ORF classes, which displayed different size, conservation, organisation, translation, structure, and amino acid preference that each different class would represent a step in gene, protein and peptide evolution.…”
Section: Introductionmentioning
confidence: 98%
“…For instance, lncORFs and upstream ORFs (uORFs) both have a very similar median ORF size (22-24 codons), and they are found in polycistronic arrangements within the transcript. Generally, the conservation scores of these two ORF classes are low, their codon usages are not random but are different from canonical proteins, and despite being translated their translational efficiency is low in comparison with canonical proteins (Aspden et al, 2014;Couso and Patraquim, 2017;Patraquim et al, 2020;Patraquim et al, 2022). Although, several uORFs and lncORFs encode peptides with important cellular functions (Magny et al, 2013;Anderson Douglas et al, 2015;Matsumoto et al, 2017;Jayaram et al, 2021) the majority of uORF and lncORF classes appear to function as translational regulators of main ORFs and in a variety of non-coding regulatory functions respectively (Aspden et al, 2014;Couso and Patraquim, 2017;Patraquim et al, 2020;Patraquim et al, 2022).…”
Section: Introductionmentioning
confidence: 99%